Waroeng Steak: Spritual Company in the Context of Post-Capitalism - Qamariyah, Faihatul (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2017)
‘Management’ at the business capitalism covers the vehicle of some aspects including the employee, course, service, network, and any kind of stuffs related to this case. In line with the system of business management, every single company might be in uniformity according to the common standard of capitalism despite having differences in the vision and mission. In this case, Waroeng Steak (WS) Restaurant in Demangan, Yogyakarta intentionally applied Islamic spiritual management. WS uses several kinds of teachings and trainings according to Islamic Sharia in the daily process. This concept concerns to the employees’ behavior upgrading and company progression through WS’ timeline program including daily, weekly, and annually activity striving for a great spiritual and economic orientation in the future. This paper argue despite the spiritual training for employees of WS might not be considered practical by capitalist standard, it is effective in bringing both spiritual and economic benefits to both company and all members of the staff. The research result that capitalism meet religion in terms of the production could lead to another standpoint at the collaborative intention in gaining positive benefit in successful business operation. Religion in regard to spiritual management in business has a significant role in bringing both individual upgrading in the class of devotion to God and the reflection to the good ethic in undergoing the working process, it is finally so-called a spiritual company that will be distinctively differ from the other existential companies. Keyword: spiritual management, employees’ habit, company characteristic upgrading